(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate the efficiency of eucalyptus citriodora (Corymbia citriodora) extract on pest damage and broccoli (Brassica oleracea) productivity. Four treatments were tested: T1: without application of the vegetal extract; T2: applications in the proportion of 50% of vegetal extract; T3: applications in the proportion of 100% of vegetal extract and; T4: application of the vegetal extract in the proportion of 1.5 times a dose, that is, 150%. There is an area of leaf attack, a mass of inflorescence and diameter of the heads, and a production of cabbage. No statistically significant differences were observed between the proportion of extract. However, an average production of inflorescence masses above the surveyed average was observed, reaching up to 53 tons per hectare. In addition, there has been a tendency for the eucalyptus plant extract to control or decrease or attack insects on the broccoli. With respect to broccoli productivity, in the same income yields above the registered means surveyed, most of the time instead of a productivity traditionally obtained.